Influence of Ease of Use and E-Service Quality on Intention to Reuse with Customer Satisfaction as a Mediating Variable in Online Travel Agent Traveloka - Daifa Al Quthni, Muhammad; Suharyanto, Suharyanto; Magdalena, Pamela (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
The rapid development of technology and the opportunities within the tourism sector in Indonesia have been significantly influenced by the emergence of online travel agents (OTAs), which have made tourism activities more effective and efficient. This study aims to analyze the impact of perceived ease of use and e-service quality on intention to reuse, with customer satisfaction serving as a mediating variable in the context of the online travel agent Traveloka. The research employs the structural equation modeling - partial least squares (SEM-PLS) method, using smart PLS 4.1.0.3 as the analysis tool, based on data from 100 respondents in the Greater Jakarta area (Jabodetabek) who use Traveloka. The results of the study indicate that perceived ease of use significantly influences intention to reuse, perceived ease of use significantly influences customer satisfaction, e-service quality significantly influences intention to reuse, e-service quality significantly influences customer satisfaction, customer satisfaction significantly influences intention to reuse, perceived ease of use influences intention to reuse with customer satisfaction as a mediating variable, and e-service quality influences intention to reuse with customer satisfaction as a mediating variable. This study shows that user satisfaction has a significant mediating role between e-service quality and reuse intention, which has not been widely discussed in previous studies. These results deepen the understanding of how factors related to user experience can increase retention of digital payment services. Abstrak - Perkembangan teknologi dan peluang sektor pariwisata di Indonesia berkembang pesat dengan menghadirkan online travel agent yang membantu kegiatan pariwisata menjadi efektif dan efisien. Penelitian ini bertujuan untuk menganalisis pengaruh kemudahan penggunaan dan e-service quality terhadap minat menggunakan kembali dengan kepuasan pengguna sebagai variabel mediasi pada online travel agent Traveloka. Penelitian dilakukan dengan menggunakan metode structural equation model - partial least square (SEM-PLS) dengan alat analisis smart PLS 4.1.0.3 berdasarkan data dari 100 responden di wilayah Jabodetabek yang menggunakan Traveloka. Hasil penelitian menunjukkan kemudahan penggunaan berpengaruh terhadap minat menggunakan Kembali, kemudahan penggunaan berpengaruh terhadap kepuasan pengguna, e-service quality berpengaruh terhadap minat menggunakan Kembali, e-service quality berpengaruh terhadap kepuasan pengguna, kepuasan pengguna berpengaruh terhadap minat menggunakan Kembali, kemudahan penggunaan berpengaruh terhadap minat menggunakan kembali dengan kepuasan pengguna sebagai variabel mediasi, dan e-service quality berpengaruh terhadap minat menggunakan kembali dengan kepuasan pengguna sebagai variabel mediasi.